Canaries in the Urban Data Mine: Analytics for Smarter City Life - KAUFFMAN, Robert J. (Institutional Knowledge at Singapore Management University, 2014)
Technology-based sensors and data analytics have created unprecendented levels of informedness for consumers, corporations, the public and government agencies. The information they generated provides a basis for smarter cities and more sustainable urban living.